La lectura de cuentos como estrategia didáctica para mejorar la comprensión lectora en estudiantes de educación secundaria - Avalos Torres, Miguel Angel (2021)
The professional sufficiency report "The reading of stories as a didactic strategy to improve _x000D_ reading comprehension in secondary school students" theoretically and pedagogically _x000D_ supports a learning experience of the Communication Area, placing it, in addition, in the line _x000D_ drawn up by the Ministry of Education, without neglecting the considerations of the context _x000D_ in which the student operates._x000D_ Considering the importance of the educational process in the construction of the knowledge _x000D_ that people need for their personal development and that of society, within the curricular _x000D_ framework by competencies, as well as by a context in which competitiveness is one of the _x000D_ elements most important for personal success, reading constitutes an element that not only _x000D_ develops the cognitive structures of students, by allowing them access to knowledge of the _x000D_ current world or the historical evolution of societies, but also enables the development of _x000D_ their mental processes superior, since it activates many parts of the brain that determine _x000D_ actions aimed at enhancing their emotions, skills and comprehensive skills, with the _x000D_ consequent benefits, both in learning and in the execution of their intellect._x000D_ In this sense, it is extremely necessary to provide the student with elements that allow him _x000D_ to better exercise his role as a builder of his own knowledge, through learning and putting _x000D_ his higher mental processes into practice, which is why, in this case, it is resorted to a strategy _x000D_ based on the reading of stories, especially those related to thematic of their environment, at _x000D_ the same time that they are easy to read and interpret, starting from the very elements that _x000D_ make up their natural and social reality.